IMPLEMENTASI AUGMENTED REALITY PADA APLIKASI PEMBELAJARAN PENGENALAN PLANET TATA SURYA - Raihan Anmar Widyasmoro; Adityo Permana Wibowo (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The lack of knowledge about solar system information for elementary school students is still a problem that cannot be overcome until now. Developing technology can make a very influential contribution to these problems, therefore this research proposes the implementation of Augmented reality (AR) technology in the context of solar system learning applications. This application is designed with features that can provide interactive and visual information in real-time. Development is carried out using the SDLC method which is a structured method for software development, in the development of the testing phase using the beta testing method with the type of Blackbox testing, with this application students can do more interesting and effective learning so that students' understanding of solar system material is increasing and students are more eager to find out the next materials because of the very interesting presentation. The positive impact when the application is implemented to students is very significant and the learning process does not feel boring for students when the learning process takes place, after being evaluated with the quiz feature student understanding increases. With the results of the tests carried out stating that in the learning system there are no features that fail when run in the sense that the system is feasible to use.